Dividend policy and firm performance: a study of listed manufacturing firms in sri lanka - Atchyuthan, N. (University of Jaffna, 2016)
This study basically investigates the relationship between the firm performance and dividend policy ratios among listed manufacturing firms in Sri Lanka. It also looks at the relationship between earnings per share, price earnings ratio, dividend payout and firm size. The annual reports for the period 2010-2014 were utilized as the source of data collection firms. The regression analysis method was employed as a statistical technique for analyzing the data collected. Our study suggests that firm performance is highly relevant to an understanding of corporate dividend policy and the results of the study find that the dividend policy is more relevant to determine the firm performance of Sri Lankan manufauring companies. The study also revealed that dividend payout and earnings per share has a significant impact on the firm performance.
Keywords: Firm performance; Earnings per share; Dividend policy; Dividend payout; Sri lanka